The Forms of Russian - Gribble, Charles E. (Book collections on Project MUSE., 2014)
"The Forms of Russian gives a thorough account of Russian morphology and morphophonemics pitched at intermediate to advanced learners of Russian, and is especially suited for a course in the structure of Russian for Russian majors and beginning graduate students. It has two principal goals: 1) to give an explicit description of many aspects of Russian declension and conjugation (including stress placement) without introducing a great deal of theoretical superstructure and formalism; and 2) to demonstrate how we can establish a systematic description of Russian, and identify the data and issues which are most important in this kind of description. A serendipitous side effect is to demonstrate the principles of structural linguistics through the laboratory of Russian morphology. The book is written in a lively, personal style and is richly accompanied by examples and exercises designed to encourage thinking and understanding rather than rote memorization."--